(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: In this study, we aimed to explore the perception of physician about medication safety in the Kingdom of Saudi Arabia.Methods: In this cross-sectional survey, we aimed to explore the perception of physician about medication safety in Saudi Arabia. We used a self-reported electronic survey questionnaire and distributed it to physicians, from intern to consultant, and specialists in Saudi Arabia. The survey collected demographic information of the physicians and about the perception of medication safety in medical care. Besides, the perception of barriers prevents off implementation of the medication safety system in medical care. We used 5-point Likert response scale system with close-ended questions to obtain responses. The data were collected through the Survey Monkey system and analyzed with the use of Statistical Package of Social Sciences (SPSS), Jeffery’s Amazing Statistics Program (JASP), and Microsoft Excel (version 16) software.Results: A total of 253 physicians responded to the questionnaire, with the majority of them belonged to the central region 73 (54.07%), with statistically significant difference among the areas (p<0.01). Most of the responders were in the age group of 24–35 years 72 (59.02%) with statistically significant differences between all age groups (p<0.01). Most of the physicians were General Practitioners 32 (27.59%), residents 31 (26.72%), and specialists 22 (18.97%) with statistically significant differences between all qualification levels (p<0.05). The average score of Perception of Physician about Medication Safety was (3.13) with high scores obtained for the element was 'the physician felt the continuing education should include the medication's safety (3.33).' and 'the physicians believed that Medication’s wastage services are essential in medical care (3.30).' The average score related to 'perceptions of barriers prevent you from implementing medication safety in medical and surgical care was 3.13. The highest score for the element implemented was a report that would generate extra work (3.34) and an uncertain association between the dental drugs and safety-related issues (3.33) with statistically significant difference between answers (p<0.05).Conclusion: In this study, the Perception of Physician about Medication Safety aspects or obstacles of implementation was found to be inadequate in Saudi Arabia. Therefore, implementing periodic education and training in medication safety in medical care are highly recommended to improve the medication safety aspects in medical care in Saudi Arabia.